2014
DOI: 10.1021/la402432q
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Behavior and Activity of Laccase and Bilirubin Oxidase on Bare Gold Surfaces

Abstract: Two blue multicopper oxidases (MCOs) (viz. Trametes hirsuta laccase (ThLc) and Myrothecium verrucaria bilirubin oxidase (MvBOx)) were immobilized on bare polycrystalline gold (Au) surfaces by direct adsorption from both dilute and concentrated enzyme solutions. The adsorption was studied in situ by means of null ellipsometry. Moreover, both enzyme-modified and bare Au electrodes were investigated in detail by atomic force microscopy (AFM) as well as electrochemically. When adsorbed from dilute solutions (0.125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 46 publications
8
74
0
Order By: Relevance
“…5A). Following our recent report, one could suggest that the poor stability of the biocathodes was, in all likelihood, attributable to BOx deactivation on the bare Au surface [34], whereas CDH was protected from the metal surface by the thiol layer.…”
Section: Resultsmentioning
confidence: 80%
“…5A). Following our recent report, one could suggest that the poor stability of the biocathodes was, in all likelihood, attributable to BOx deactivation on the bare Au surface [34], whereas CDH was protected from the metal surface by the thiol layer.…”
Section: Resultsmentioning
confidence: 80%
“…Recovering of the catalytic signal for H 2 oxidation after surfactant addition in the R. eutropha Hase sample suggested that the absence of a surfactant compared to the A. aeolicus Hase sample induced structural changes of the enzyme because of the strong electrostatic interactions. LAC and BOD immobilized for DET on gold electrodes were shown to face potential-induced structural changes as revealed by SERRS and ellipsometry experiments [58,141]. QCM and dual-polarization interferometry studies of BOD immobilized on negative SAM-based gold electrodes highlighted that deformation required for DET should lead to a decrease in activity at high enzyme concentrations [146].…”
Section: Future Directions: Towards Rational Bioelectrode Designmentioning
confidence: 99%
“…Hence, polycrystalline gold surfaces, where the distribution of metal atoms is nonuniform throughout the electrode surface, are very handy. Surface treatment provides surface control and promotes their wide use for protein electrochemistry [58]. Electrochemical cleaning by cycling in H 2 SO 4 solution between −0.35 V and +1.5 V vs. Ag/AgCl allows calculating of the real electroactive surface area by integrating the gold oxide reduction peak at +0.9 V, taking into account a charge of 390 µC·cm −2 for the reduction of a gold oxide monolayer [59].…”
Section: Conductive Electrode Surfacesmentioning
confidence: 99%
“…When enzymes adsorb on a solid electrode, enzymes might tend to denature and to lead to decrease in their catalytic functions due to conformational change [5][6][7][8]. Elucidation of the adsorbed enzyme conditions and controlling of the adsorption state will lead to improvement in the DET-type catalytic performance and a wide variety of its applications, such as biosensors and biofuel cells.…”
Section: Introductionmentioning
confidence: 99%